Origins of the Establishment of the Politico-Legal Basis for Relations between Ukraine and the Republic of Lithuania (1989–1994) - Pohuliaiev, Oleksandr (Український політико-правовий дискурс, 2025)
The relevance of this study stems from the need for a profound understanding of the origins of the legal foundations of Ukrainian-Lithuanian relations in the context of contemporary challenges associated with European integration, international cooperation, and global geopolitical transformations. In the current environment, as Ukraine and the Republic of Lithuania actively counter external threats, particularly Russian aggression, and strive for deeper integration into the European legal and political space, analyzing the historical prerequisites for the development of their bilateral relations assumes particular significance. Examining the legal framework established between 1989 and 1994 enables not only an assessment of the contribution of these relations to strengthening the sovereignty of both states but also the identification of lessons for contemporary diplomacy aimed at countering hybrid threats, enhancing international security, and upholding democratic values. Furthermore, the topic’s relevance is underscored by the need to refine mechanisms for legal interaction within international organizations, such as the European Union, where Ukraine and Lithuania jointly advocate for their interests. The purpose of the article is to analyze the legal framework for the formation of bilateral relations between Ukraine and the Republic of Lithuania in 1989–1994, focusing on the legal nature, significance, and impact of key agreements on the establishment of the international legal status of both states. The research methodology combines historical-chronological, comparative, and systemic approaches with an interdisciplinary analysis of legal, political, and historical aspects. The resultsdemonstrate that informal contacts between the People’s Movement of Ukraine and the Lithuanian Sąjūdis movement laid the groundwork for legally formalized bilateral relations, which facilitated the development of a legal framework for cooperation. The agreements concluded between 1991 and 1994 became the foundation for strengthening the international legal status of Ukraine and Lithuania, as well as their integration into the European legal space. The conclusions of the study contribute to the improvement of modern mechanisms of interstate cooperation, in particular in the field of bilateral trade, economic and legal obligations.